Effective valorization of agro‐waste of castor oil extraction industry as feedstock for sustainable fish production. (12th May 2021) - Jayant, Manish; Sahu, Narottam P.; Deo, Ashutosh D.; Garg, Chetan K.; Yadav, Rohitash; Gupta, Subodh
Abstract: Castor protein isolate (CPI) was prepared by aqueous solubilization of defatted castor kernel meal under alkaline conditions (pH 12.0), with precipitation at the isoelectric point (pH 5.0) followed by heat treatment. Five experimental diets were prepared by substituting soybean protein isolate (SPI) at 0%, 25%, 50%, 75%, and 100% with CPI based on protein equivalent basis. The diets were assigned as control, PI25, PI50, PI75, and PI100, respectively. A 60‐day feeding trial was conducted following a completely randomized design. Results revealed significant improvement in growth rates, feed conversion, and protein retention in Labeo rohita fingerlings ( P  < 0.05) at 124.50 g CPI kg −1 diet (PI75 ). However, these were similar between control and PI100 ( P  > 0.05). Dietary CPI did not alter the hepatosomatic index, viscerosomatic index, survival, carcass composition (except crude protein), and digestive enzymes ( P  > 0.05). The metabolic enzymatic profile of rohu fingerlings was significantly affected due to dietary treatments ( P  < 0.05) but oxidative stress enzymes were not affected by feeding of CPI. The activity of the aminotransferases, lactate dehydrogenase, and malate dehydrogenase did not differ ( P  > 0.05) between control and PI100 . The preparation of protein isolate is therefore a way forward for the effective valorization of toxic castor meal and could be used at 164.0 g kg −1 inclusion (complete substitution of soybean protein isolate) in the diet of L. rohita . © 2021 Society of Industrial Chemistry and John Wiley & Sons Ltd.